The The Influence of Health Coaching in Controlling Blood Sugar in Type 2 Diabetes Mellitus Patients: A Systematic Review - Sulfikar, Andi; Irwan, Andi Masyitha; Restika, Indah (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Physiologically, DM patients' blood sugar control is affected by stress, but it can also interfere with their ability to regulate themselves in carrying out daily care. Objective: This study aims to identify and analyze available scientific evidence about the effect of Health Coaching (HC) in controlling blood sugar in type 2 DM patients. Method: This systematic review is based on the PRISMA checklist. Literature search via PuBMED, Science direct, google scholar, cochrane, and wiley. Structured research questions used the PICO electronic method (patient, intervention, comparison and outcome). Results: The number of respondents who suffered from type 2 DM was 6,169 with the longest treatment time of 3 years. There are 4 interventions found in controlling blood sugar in type 2 DM patients, namely HC using web-based coaching techniques, HC using a telephone, face-to-face HC using a smartphone, and HC using an application. cell phone called MDMA (diabetes management mobile app). Conclusion: Interventions that were found as HC techniques to control blood sugar in type 2 DM patients were Health coaching with web-based coaching techniques, HC conducted using the telephone, HC conducted face to face using a smartphone, and HC using a cellular mobile application called MDMA (application cellular diabetes management). However, several things that became the main limitations of this review of this study were the absence of a standard in determining the duration of HC interventions, so the duration of HC in each study varied and the longest duration was up to 3 years. Recommendation: Therefore, further research is needed regarding the standard of HC intervention in controlling blood sugar in diabetes mellitus patients.